First Report of Rust Caused by Puccinia xanthii on Xanthium orientale subsp. italicum in China - Zhao, Y-Z (Plant disease, 2014)
Xanthium orientale subsp. italicum (Moretti) Greuter is an annual herbaceous plant in the Asteraceae family, native to North America. It was first found in Beijing, China, in 1991. Since then, it has spread into many provinces such as Heilongjiang, Jilin, Liaoning, Hebei, Shandong, Xinjiang, and so on. Furthermore, it has been listed as one of the dangerous quarantine weeds in China (4). This noxious invasive weed has a strong ability to acclimatize to new environments. X. orientale subsp. italicum can usually be found in alluvial flatlands, riverbanks, wastelands, roadsides, pastures, as well as farmlands. The presence of this plant decreases the native biodiversity and influences the production of agriculture and stockbreeding. In August 2013, a rust disease was first observed on X. orientale subsp. italicum in Dalian, Liaoning Province, northeast China. Various sized lesions were found on approximately one third of the leaves of each infected plant. These lesions were yellow in the early stage of infection; gradually the center of each lesion turned brown, and eventually the infected lesions became necrotic and ruptured. The small (on average 4 mm in diameter) and dark brown raised telia appeared in the center of the lesions on the lower leaf surface. The teliospores were brown, clavate, two-celled, and measured 42 to 58 × 12 to 21 μm. Teliospores had a conical top, constricted septa, and a persistent pedicel (22 to 70 μm in length). The walls of the teliospores were smooth, 0.8 to 1.2 μm thick at the side and 4 to 8 μm thick at the apex. The size, color, and morphology of the teliospores fit the description of Puccinia xanthii (1,3). A pathogenicity test was conducted by the method of detached leaf inoculation (2). We collected 48 healthy leaves from six individuals of X. orientale subsp. italicum plants, eight from each individual. Teliospores from disease samples were suspended to 1 × 105 spores per ml with sterile water and then smeared on 24 leaves (four per individual); the remaining leaves were inoculated with sterile water as control. Each of the leaves was put on a moist filter paper in a petri dish, and was cultured in a chamber with a 12-h photoperiod at 25°C. Seven days later, dark brown raised telia were observed on all inoculated leaves but not on control ones. The teliospores were removed from the sorus on inoculated leaves, and according to the morphology confirmed to be those of P. xanthii. The rust caused by P. xanthii has been documented in different hosts in many other countries such as Spain, France, Italy, former Yugoslavia, Australia, the United States, and South Africa. In addition, the rust fungus was found to infect X. orientale subsp. italicum in eastern Hungary (1). To our knowledge, this is the first report of P. xanthii attacking the invasive plant X. orientale subsp. italicum in China. It is important to study the potential of using this rust fungus as a biological control agent of X. orientale subsp. italicum. This work was supported by the Project of the National Natural Science Foundation of China (31270582). References: (1) I. Dávid et al. Plant Dis. 87:1536, 2003. (2) Z. D. Fang. Research Methods of Plant Disease, 1998. (3) J. A. Parmelee. Can. J. Bot. 47:1391, 1969. (4) F. H. Wan et al. Biological Invasion: Color Illustration of Invasive Alien Plants in China, 2012